Ultrasound of Normal and Injured Ligaments and Retinacula of the Hand - McCarthy, Catherine L. (Seminars in Musculoskeletal Radiology, 2020)
Clinical diagnosis of ligament and retinacular injuries of the hand may be challenging. Ultrasound (US) enables detailed high-resolution, dynamic, and real-time evaluation of these structures. This article is a comprehensive review of the intricate anatomy, optimal imaging technique, and normal US appearances of these ligaments and retinacula. The US features, pertinent biomechanics, clinical presentation, and differential diagnosis of injuries affecting the annular pulleys, differentiating from climber's finger; extensor hood including sagittal band and central slip rupture; proximal interphalangeal and metacarpophalangeal collateral ligaments including the Stener lesion and associated volar plate injury; and the anterior oblique or beak ligament of the trapeziometacarpal joint are reviewed. Emphasis is placed on optimal transducer positioning, value of dynamic US, injury severity, surgical indications, and other US findings with important management implications. US facilitates a timely accurate diagnosis of hand ligament and retinacular injury to ensure optimal patient management and minimize the risk of functional impairment of the hand.
Keywords: ultrasound; hand retinacula; annular pulley; extensor hood; central slip; sagittal band; collateral ligament; Stener lesion; anterior oblique ligament; beak ligament